Clinical Outcomes of Scleral Buckling combined with Vitrectomy Pars Plana for Rhegmatogenous Retinal Detachment: Oral Presentation - Observational Study - Resident - Andry Lukandy; Sumanti, Eugeni (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesThe various types of primary interventions for rhegmatogenous retinal detachment (RRD) includepars plana vitrectomy (PPV), scleral buckling (SB), and combination of both. Intraocular tamponadewith silicone oil (SO) or expanding gas. This research was conducted to evaluate the clinicaloutcomes of SB combined with PPV as a treatment for RRD. MethodsThis research was prospective descriptive study with total sampling for RRD treated by SB combinedwith PPV from August 2022 to January 2023 in RSUP. Prof. Dr. R.D. Kandou. We observed the BCVA,IOP before and after the surgeries. Clinical findings, intraocular tamponade and complications afterthe surgeries were observed. ResultsMost of the patients was male with average age of 28 ± 40 years. RRD was observed in 6 eyes andlaterality on right eye. BCVA was 2.5 ± 2 logMAR before the surgery and 2.3 ± 1 logMAR 1 monthafter the surgery. Preoperative IOP was 7 ± 11 mmHg and 13.6 ± 10 mmHg 1 month after thesurgery. Macular detachment, 1 Quadrant Detachment, 1 Number of retina break mostly on superotemporalquadrant were found the most. Proliferative vitreoretinopathy was found in 1 eye.Intraoperative triamcinolone used in 4 eyes and perfluorocarbon in 1 eyes. Subconjunctival bleedingwas found the most, followed by corneal edema and subretinal hemorrhage as postoperativecomplications respectively. ConclusionThere were several clinical condition seen such as BCVA after the surgery that didn’t improve asexpected, High IOP found in several eyes and subconjunctival bleeding was the complication foundthe most in these eyes.